ASPECTS OF LANGUAGE LEARNING (Scientific journal of the Fergana State University, 2023)
The purpose of the present study is to reveal the results of the study of language learning strategies of foreign language learners. In the article, the methods and ways of language learning based on modern trends are presented through examples, and the experiences of scientists and students researching foreign languages are studied. The advantages of creating an individual strategy through the consistent use of Internet networks and platforms in foreign language learning have been widely discussed.